Predicting the coefficient of thermal expansion for textile composites based on a unit cell approach - Brown, Louise P.; Zeng, Xuesen; Long, Andrew C.; Brooks, Richard; Jones, I. Arthur (2013)
The study focuses on unit cell FE modelling to predict coefficients of thermal expansion (CTEs) for sheared fabric laminates. Shear, as a dominant deformation mode in textile composites forming, introduces high degrees of anisotropy in both elasticity and thermal expansion. The unit cell predictions are based on realistic fibre architecture and measured material properties of constituent fibre and resin. Under the multi-scale framework, the unit cell predictions are part of the essential input data for locally varied material definitions. These definitions are used to model structural components to predict shape distortion. The FE model gives predictions close to the experimental data, when the boundary conditions are correlated to the coupon size. Nesting is an influential factor for CTEs. For true material representation, in-plane periodicity and nesting have been considered.